Histamine reactivity during the refractory period after exercise induced asthma. - Hahn, A G (1984)
An episode of exercise induced asthma will usually be followed by a period during which further exercise will not induce asthma. Postulated mechanisms include persistence of catecholamines released during exercise, development of tolerance to released mediators, and mediator depletion. To investigate the underlying mechanism further eight asthmatic men underwent three experimental protocols as follows: two treadmill runs of eight minutes; two incremental challenges with histamine inhalation; and a treadmill run of eight minutes followed by an incremental challenge with histamine inhalation. In each case the two challenges began 40 minutes apart. Patients performed the paired exercise trial first. Refractoriness to bronchoconstriction was shown in the repeated exercise studies but did not occur with repeated histamine challenge. The geometric mean histamine concentrations required to produce a 20% fall in forced expiratory volume in one second (FEV1) were 1.53 mg/ml and 0.93 mg/ml for the first and second challenges respectively (NS) and 1.4 mg/ml (NS) for the histamine challenge after exercise. It is concluded that refractoriness to exercise induced asthma is not explained by the development of smooth muscle tolerance to repeated histamine exposure or by the persistence of catecholamines released during exercise. The data are consistent with the theory of mediator depletion as the cause of refractoriness.